The curative effect of traditional Chinese medicine compounded medications in relieving racewalking fatigue - Ma, T. (Revista Brasileira de Medicina do Esporte, 2021)
Racewalking fatigue is a kind of fatigue symptom after a period of racewalking, which may lead to limb weakness, mental fatigue, muscle fatigue and other phenomena. If we do not timely adjust the stretching and effective treatment after exercise, it is very easy to produce sports injury and seriously affect the athletes` physical function. In order to effectively alleviate the fatigue of racewalking, this study focused on the traditional Chinese medicine (TCM) compounded medication, analyzed the mechanism of action and medicinal effectiveness of the TCM compound, and carried out control experiment on 80 male ICR mice. The mice in the experimental group were given sedentary training and racewalking training in groups. The results showed that the two groups of ICR mice, after racewalking training, had exercise fatigue symptoms and a large amount of serum lactic acid and other substances, while mice in group D treated by gavage of traditional Chinese medicine compounded medication had the symptoms of exercise fatigue, but the contents of blood urea nitrogen and lactic acid were decreased, the gastrocnemius muscle fibers were evenly arranged, the transverse lines were neat, and a rebound of protein expression. This shows that Chinese medicine compound can play a significant role in relieving racewalking fatigue.